Fluorescence and Morphology of Self‐Assembled Nucleobases and Their Diphenylalanine Hybrid Aggregates. Issue 65 (25th October 2019) - Avitabile, Concetta; Diaferia, Carlo; Roviello, Valentina; Altamura, Davide; Giannini, Cinzia; Vitagliano, Luigi; Accardo, Antonella; Romanelli, Alessandra
Abstract: Studies carried out in recent decades have revealed that the ability to self‐assemble is a widespread property among biomolecules. Small nucleic acid moieties or very short peptides are able to generate intricate assemblies endowed with remarkable structural and spectroscopic properties. Herein, the structural/spectroscopic characterization of aggregates formed by nucleobases and peptide nucleic acid (PNA)–peptide conjugates are reported. At high concentration, all studied nucleobases form aggregates characterized by previously unreported fluorescence properties. The conjugation of these bases, as PNA derivatives, to the dipeptide Phe–Phe leads to the formation of novel hybrid assemblies, which are characterized by an amyloid‐like association of the monomers. Although these compounds share the same basic cross‐β motif, the nature and number of PNA units have an important impact on both the level of structural order and the intrinsic fluorescence of the self‐assembled nanostructure. Abstract : Coming together to shine : Natural nucleobases aggregate in water and emit fluorescence. If nucleobases within a peptide nucleic acid backbone are conjugated to the N terminus of Phe–Phe, aggregation occurs at lower concentrations. In the PNA–Phe–Phe conjugates, the Phe–Phe moiety directs the formation of antiparallel stacks that show fluorescence in either solution or solid states (see figure).